2008
DOI: 10.1088/0264-9381/25/16/162002
|View full text |Cite
|
Sign up to set email alerts
|

A universal inequality between the angular momentum and horizon area for axisymmetric and stationary black holes with surrounding matter

Abstract: We prove that for sub-extremal axisymmetric and stationary black holes with arbitrary surrounding matter the inequality 8π|J| < A holds, where J is the angular momentum and A the horizon area of the black hole.PACS numbers: 04.70.Bw, 04.40.-b, 04.20.Cv preprint number: AEI-2008-034 ‡ Note that in [1] a more general conjecture, incorporating the black hole's electric charge Q, was formulated. Here we prove this conjecture for the pure Einstein field, i.e. for Q = 0, and vanishing cosmological constant Λ = 0. (I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
98
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(99 citation statements)
references
References 4 publications
1
98
0
Order By: Relevance
“…In this context, an alternative (but related) bound on the angular momentum can be formulated in terms of a horizon area-angular momentum inequality A ≥ 8π|J|. This inequality was conjectured for the non-vacuum axisymmetric stationary case (actually, including the charged case) with matter surrounding the horizon in [8] and then proved in [9][10][11], whereas its validity in the vacuum axisymmetric dynamical case was conjectured and discussed in [12], partial results were given in [13,14] and a complete proof in [15]. Equality holds in the extremal case.…”
mentioning
confidence: 99%
“…In this context, an alternative (but related) bound on the angular momentum can be formulated in terms of a horizon area-angular momentum inequality A ≥ 8π|J|. This inequality was conjectured for the non-vacuum axisymmetric stationary case (actually, including the charged case) with matter surrounding the horizon in [8] and then proved in [9][10][11], whereas its validity in the vacuum axisymmetric dynamical case was conjectured and discussed in [12], partial results were given in [13,14] and a complete proof in [15]. Equality holds in the extremal case.…”
mentioning
confidence: 99%
“…These studies considered axisymmetric and stationary BHs surrounded by matter [1,2]. In some cases, Maxwell fields were also included [3].…”
mentioning
confidence: 99%
“…J(H t ) = J. Moreover, at every time slice {t} the universal inequality 8π J ≤ A(H t ) holds [16], [8], [14] and we also expect the validity of the Penrose inequality A(H t ) ≤ 8πM 2 , where M is the ADM-mass which is also conserved. Thus, in this scenario we have J(H t ) = J, 8π J ≤ A(H t ) and we expect to have A(H t ) ≤ 8πM 2 .…”
Section: Introductionmentioning
confidence: 78%
“…Secondly, we found that rotation stabilizes the shape of stable horizons to such an extent that rotating holes of a given area and angular momentum have their entire shapes controlled (and not just their global measures like R or L). This is manifest from the pointwise bounds (14) σ…”
Section: Introductionmentioning
confidence: 99%